Requesting conflicts of interest declarations from the European Medicines Agency: 3-year follow-up status - K. Boesen; P. C. Gøtzsche; J. P. A. Ioannidis (Cambridge University Press, 2024)
Abstract Aims We have previously described the European Medicines Agency's (EMA) and the US Food and Drug Administration's guidelines, each for a specific psychiatric indication, on how to design pivotal drug trials used in new drug applications. Here, we report on our efforts over 3 years to retrieve conflicts of interest declarations from EMA. We wanted to assess potential internal industry influence judged as the proportion of guideline committee members with industry conflicts of interest. Methods We submitted Freedom of Information requests in February 2020 to access EMA's lists of committee members (and their declared conflicts of interest) involved in drafting the 13 'Clinical efficacy and safety' guidelines available on EMA's website pertaining to psychiatric indications. In our request, we did not specify the exact EMA committees. Here, we describe the received documents and report the proportion of members with industry interests (i.e. defined as any financial industry relationship). It is a follow-up paper to our first report (http://doi.org/10.1017/S2045796021000147). Results After 2 years and 9 months (November 2022), the EMA sent us member lists and corresponding conflicts of interest declarations from the Committee for Medicinal Products for Human use (CHMP) from 2012, 2013 and 2017. These member lists pertained to 3 of the 13 requested guidelines (schizophrenia, depression and autism spectrum disorder). The 10 remaining guidelines were published before 2011 and EMA stated that they needed to require permission from their expert members (with unknown retrieval rate) and foresaw excessive workload and long wait. Therefore, we withdrew our request. The CHMPs from 2012, 2013 and 2017 had from 34 to 36 members; 39%-44% declared any interests and we judged 14%-18% as having industry interests. For the schizophrenia guideline, we identified two members with industry interests to companies who submitted feedback on the guideline. We did not receive declarations from the Central Nervous System (CNS) Working Party, the CHMP appointed expert group responsible for drafting and incorporating feedback into the guidelines. Conclusions After almost 3 years, we received information, which only partly addressed our request. We recommend EMA to improve transparency by publishing the author names and their corresponding conflicts of interest declarations directly in the 'Clinical efficacy and safety' guidelines and to not remove conflicts of interest declarations after 1 year from their website to reduce the risk of stealth corporate influence during the development of these influential guidelines.